Marked Tourist Paths in Polish National Parks - Styperek, Jarosław (Turyzm/Tourism, 2001)
The article presents the current condition of marked tourist paths, one of the elements of tourist infrastructure in national parks. The author has made a comparative analysis of the length and density of such paths in all the Polish national parks. He also presents the concept known as a ‘system of linear recreational accessibility’ which allows the connectivity and pattern of the marked path network in individual parks to be described.